2020
DOI: 10.1101/2020.01.07.897439
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Atomistic basis of microtubule dynamic instability assessed via multiscale modeling

Abstract: Microtubule "dynamic instability," the abrupt switching from assembly to disassembly caused by the hydrolysis of GTP to GDP within the β subunit of the αβ-tubulin heterodimer, is necessary for vital cellular processes such as mitosis and migration. Despite existing high-resolution structural data, the key mechanochemical differences between the GTP and GDP states that mediate dynamic instability behavior remain unclear. Starting with a published atomic-level structure as an input, we used multiscale modeling t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
(110 reference statements)
0
1
0
Order By: Relevance
“…These nonequilibrium processes not only allow stable finite-length distributions, but also structural dynamics, such as actin treadmilling and microtubule dynamical instability, that allow the cellular cytoskeleton to rapidly respond and reconfigure to environmental cues. Using models ranging from idealized onedimensional filaments to geometrically realistic particlebased dynamical simulations (Bollinger and Stevens, 2018;Fai et al, 2019;Hemmat and Odde, 2020;Mohapatra et al, 2016;Tong and Voth, 2020), researchers have identified multiple mechanisms by which active filament assembly/disassembly processes and energy-driven subunit conformational changes can lead to 1D filaments which exhibit dynamical instabilities and/or with welldefined stable sizes. In contrast, recall from section II.A.2 that equilibrium 1D filaments generically exhibit exponential length distributions.…”
Section: Non-equilibrium Mechanisms Of Size-controlled Assemblymentioning
confidence: 99%
“…These nonequilibrium processes not only allow stable finite-length distributions, but also structural dynamics, such as actin treadmilling and microtubule dynamical instability, that allow the cellular cytoskeleton to rapidly respond and reconfigure to environmental cues. Using models ranging from idealized onedimensional filaments to geometrically realistic particlebased dynamical simulations (Bollinger and Stevens, 2018;Fai et al, 2019;Hemmat and Odde, 2020;Mohapatra et al, 2016;Tong and Voth, 2020), researchers have identified multiple mechanisms by which active filament assembly/disassembly processes and energy-driven subunit conformational changes can lead to 1D filaments which exhibit dynamical instabilities and/or with welldefined stable sizes. In contrast, recall from section II.A.2 that equilibrium 1D filaments generically exhibit exponential length distributions.…”
Section: Non-equilibrium Mechanisms Of Size-controlled Assemblymentioning
confidence: 99%